Vibrational spectroscopy and computer modeling of proteins: solving structure of α1-acid glycoprotein. Issue 2 (2004) - Kopecký Kopecký, Vladimír Vladimír; Ettrich Ettrich, Rüdiger Rüdiger; Hofbauerová Hofbauerová, Kateřina Kateřina; Baumruk Baumruk, Vladimír Vladimír
Abstract : This work introduces a new approach connecting vibrational spectroscopy with homology and energetic molecular modeling of proteins. Combination of both methods can compensate their disadvantages and result in realistic three-dimensional protein models. The approach is most powerful for membrane proteins or glycoproteins with high carbohydrate content where X-ray or NMR analysis is not always successful. Nevertheless, it can also serve as a tool of preliminary analysis of any protein with unknown structure. Power of the approach is demonstrated on human α1 -acid glycoprotein. Its predicted structure published in [V. Kopecký Jr. et al., Biochem. Biophys. Res. Commun .300 (2003), 41–46] is discussed in detail with respect to the approach and its general employment.